Kebijakan Ekonomi Hijau Tiongkok Di Era Presiden Xi Jinping - Rizaldy Febrian Azwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jember)
World's growing number of pollution needs more serious consideration. Climate change that is currently happening as an impact of pollution threatens the life of human being globally. China, as one of the main contributors to global pollution, needs to sort their problem and answer international demand to resolve the global pollution problem as quick as possible. Therefore, they are implementing Green Economy that meant to make human activities more sustainable to address and tackle the issue. However, despite more than a decade of Green Economy implementation, China still could not meet the world's long-term demand to combat global pollution, and even has a growing pollution problem as of 2018. By using Two-level Game Theory, this study finds the reason behind China Green Economy implementation, which is to respond international urge and pressure to combat severe global pollution problem and also build a profitable long-term local economic growth at the same time.